Insights Into Magma Chamber Processes From the Relationship Between Fabric and Grain Shape in Troctolitic Cumulates - Holness, Marian B.; Morris, Charlotte; Vukmanovic, Zoja; Morgan, Dan J. (Frontiers in Earth Science, 2020)
The strength of foliations defined by shape preferred orientation of plagioclase in troctolitic cumulates from the Layered Series of the Skaergaard intrusion, and the Rum Eastern Layered Intrusion, increases as the grains become more tabular, due either to the greater propensity of highly non-equant grains to be re-arranged by magmatic currents or tectonic disruption of poorly consolidated mush, or by the effects of a pre-existing shape preferred orientation on final grain shape in fully solidified rocks. The stratigraphic evolution of grain shape, microstructures and fabrics in the lowest 320 m of the Skaergaard Layered Series records the progressive inflation of the chamber to its final size. During the earliest stages of solidification, the extent of in situ nucleation and growth on the chamber floor decreased upward through the stratigraphy, due to the development of a thermally insulating blanket of mush on the floor. An upward increase in foliation strength as the chamber inflated to its final size was a result of the increasing strength of convection of the bulk magma and an increasing contribution to the floor mush of crystals derived from the walls of the enlarging magma chamber. Plagioclase in the troctolites in the open-system magma chamber of the Rum Eastern Layered Intrusion is generally more equant than that in the Skaergaard intrusion, perhaps related to the slower crystal growth on the margins of the continuously replenished Rum chamber. Significant sub-solidus modification of original igneous microstructures is observed in Rum troctolites from parts of the stratigraphy recording frequent replenishment events.